Chemical Composition and In Vitro Biological Activity of Two Thymus L. Varieties Growing in Turkey - TAŞKIN, TURGUT; RAYAMAN, ERKAN; YILMAZ, BEYZA NUR (My University, 2024)
Thymus kotschyanus var. kotschyanus (TKK) and T. kotschyanus var. glabrescens (TKG) varieties were used as both spice and medicine by the people in Turkey. It was determined that plants’ methanol extracts had the strongest antioxidant, anticholinesterase, antiurease activity and high total phenolic contents. The ethyl acetate and methanol extracts were found to have strong antimicrobial activity. Methanol extracts showed low hemolytic effect against human erythrocytes. It was determined that TKG extract showed higher anti-proliferative effect compared to TKK extract. Both plants extract significantly decreased reactive oxygen species (ROS) generation in cancer cells. It was determined that amounts of chlorogenic and rosmarinic acid compounds were similar in both plants, but apigenin 7-O-neohesperidoside compound was found in higher amounts in TKK. The findings obtained in this study suggest that methanol and ethyl acetate extracts obtained from these two species can be used as antioxidant, anticholinesterase, antimicrobial and antiurease agents. The findings support the traditional use of these species.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; biological activity; HPLC-DAD; Thymus species